1994
DOI: 10.1002/cyto.990150409
|View full text |Cite
|
Sign up to set email alerts
|

A fast kinetic method for assessing mitochondrial membrane potential in isolated hepatocytes with rhodamine 123 and flow cytometry

Abstract: Rhodamine 123 (Rh123) is widely used as a flow cytometric probe for mitochondrial membrane potential (MMP) in metabolic, pharmacologic, and toxicological studies. However, the use of relatively high concentrations of Rh123 (up to 10 pg/ml) and prolonged incubation times (up to 1 h), including washing steps, may be inconvenient for certain applications in which labile cells are used or which demand rapid or repeated analysis. In this paper we describe a rapid kinetic assay of MMP in isolated rat hepatocytes, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 35 publications
4
52
1
Order By: Relevance
“…The data obtained with heat-killed yeast suspensions suggest that Rh123 can be used as a probe to discriminate live from dead cells. This is similar to what has been reported by Juan et al (1994) with animal cells. Actually, heat-killed yeast cells showed a diffuse and more intense fluorescence than untreated cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The data obtained with heat-killed yeast suspensions suggest that Rh123 can be used as a probe to discriminate live from dead cells. This is similar to what has been reported by Juan et al (1994) with animal cells. Actually, heat-killed yeast cells showed a diffuse and more intense fluorescence than untreated cells.…”
Section: Discussionsupporting
confidence: 92%
“…This confirmed that Rh123 fluorescence changes reflect changes of ∆Ψm, as has been described in intact animal cells (Juan et al, 1994). It has been discussed in previous work that alterations of ∆Ψm may not be the only cause of Rh123 fluorescence changes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations